Improving Wood Surface Wettability through Gas-phase Ozone Treatment of Air-dry Wood - Antti Korpela; Tetyana Koso; Kristiina Lillqvist; Lauri Rautkari; Hannes Orelma (BioResources)
An increase in wood free surface energy enhances the wettability of wood surfaces, leading to better interaction with water-based coatings. This study investigated the effect of gas-phase ozonation on the wettability of spruce, thermo-modified pine, and birch woods. The effects of the treatment were evaluated by measuring the water contact angle and the Cobb value on the wood sample surfaces, and by determining the surface free energy of the wood surfaces using the Owens, Wendt, Rabel, and Kaelble (OWRK) calculation method. Furthermore, water absorption and evaporation rates were assessed through water immersion and subsequent drying of the wood samples. The results indicated that ozone treatment increased the surface energy, and especially its polar component, thus accelerating water spreading and absorption on the wood surfaces. The most probable cause of the observed effects is the formation of new carbonyl and carboxyl groups resulting from reactions of the ozone with the wood surface. The findings suggest that the ozone treatment technique can enhance spreading, absorption, and adhesion of water-based adhesives and coatings to wood surfaces. This research may facilitate the development and use of new environmentally friendly water-based adhesives and coatings.